1996
DOI: 10.1007/bf02252937
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity and inhibitor profile of human recombinant p56lck from a baculovirus expression vector

Abstract: p56lck, a member of the src family of non-receptor protein receptor kinases, is required for normal signal transduction through the T cell receptor. Inappropriate T cell activation and proliferation has been identified as an early event in auto-immune disease-agents which control T cell activation through modulation of p56lck kinase activity could therefore be potential therapeutic agents for a range of pathological conditions. To identify p56lck inhibitors, we have established an assay system suitable for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…T cell PKC was partially purified from peripheral blood T cells by ion-exchange chromatography by the method outlined in ref 23. Bovine heart PKA (23), rabbit skeletal muscle phosphorylase kinase (24), and human recombinant p56 lck (25) and ZAP-70 (5) assays were performed as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…T cell PKC was partially purified from peripheral blood T cells by ion-exchange chromatography by the method outlined in ref 23. Bovine heart PKA (23), rabbit skeletal muscle phosphorylase kinase (24), and human recombinant p56 lck (25) and ZAP-70 (5) assays were performed as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…The first in vitro high-throughput screening study to identify enzyme inhibitors was reported in 1994, using a scintillation proximity assay . Although there are earlier reports of high-throughput screening approaches to identify enzyme inhibitors, these all used cell systems expressing the target enzyme. This first report of in vitro high-throughput screening was followed by reports of a kinase inhibitor screening campaign (using a radioactivity-based assay), and a protease inhibitor screening campaign (using a fluorescence-based assay). Since then the literature has exploded, reaching a peak of 260 publications describing HTS campaigns against specific enzymes (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Whether derived from native recognition sequences or synthetically optimized, peptide substrates are used to screen for small‐molecule inhibitors against kinases that are associated with disease (Table I). 17, 28–39 Abltide (EAIYAAPFAKKK)17 is one example of an optimized substrate that was selected by screening a degenerate peptide library against purified kinases in vitro . Abltide demonstrated a higher rate of reactivity with Abl kinase than with closely related kinases such as Src17 and is now routinely used to monitor Abl kinase activity in vitro .…”
Section: Introductionmentioning
confidence: 99%